Strengthening the Understanding of Religious Moderation at Islamic University - Muh Mawangir; Anica Anica (STAI Hubbulwathan Duri, 2023)
Religion may solve all human life problems, including violence, oppression, radicalism, terrorism, intolerance, fanaticism, and excessive behaviour in all areas of life, including education. Islamic higher education provides intellectual, social, and religious education to the community. Students, as the younger generation, lead civilization and show mature attitudes towards social issues, including rising religious issues and religious moderation. This study seeks to enhance the comprehension of religious moderation at Islamic University. This study employed a qualitative approach, utilising descriptive data analysis. Information was gathered through interviews and documents. This study included a sample of 45 students enrolled in the Islamic Education program. The results suggested that implementing Islamic education centred on religious moderation to enhance students' comprehension of religious moderation in the Islamic Religious Education programme should be achieved through instructional approaches during lectures and mutual support from the academic community, professors, and students. Therefore, enhancing comprehension of religious moderation can foster a more profound understanding of adopting a peaceful, harmonious, non-anarchic, non-fanatical, non-arrogant, courteous, and respectful approach towards differing opinions while upholding the value of unity among students in the Islamic Religious Education programme at the University.